Alternative Splicing Controls Myotonic Dystrophy Protein Kinase Structure, Enzymatic Activity, and Subcellular Localization - Wansink, Derick G.; van Herpen, René E. M. A.; Coerwinkel-Driessen, Marga M.; Groenen, Patricia J. T. A.; Hemmings, Brian A.; Wieringa, Bé (Molecular and Cellular Biology, 2003)
Article Usage Stats Services MCB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue MCB About MCB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MCB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0270-7306 Online ISSN: 1098-5549 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MCB .asm.org, visit: MCB